2023
DOI: 10.1039/d3cp01103h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of rhombus-shaped nanographenes: system size evolution from closed- to open-shell ground states

Abstract: We theoretically study and characterize a set of rombus-shaped nanographenes of increasing size, or n-rhombenes, where n = 2−6, displaying zigzag edges leading to an enhancement of the (poly)radicaloid nature...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…For example, for the GS properties of physical systems at θ el = 0, FT-DFT with F [26,38,41]. Therefore, a number of recent studies on the GS properties of physical systems at θ el = 0 [74][75][76][77][78][79][80][81] have actually been performed using TAO-DFT with…”
Section: Tao-dft (Withmentioning
confidence: 99%
“…For example, for the GS properties of physical systems at θ el = 0, FT-DFT with F [26,38,41]. Therefore, a number of recent studies on the GS properties of physical systems at θ el = 0 [74][75][76][77][78][79][80][81] have actually been performed using TAO-DFT with…”
Section: Tao-dft (Withmentioning
confidence: 99%
“…Over the last few years, TAO-DFT has been employed to explore the electronic [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], hydrogen storage [47,49,50], and spectroscopic [43,62,63] properties of gas-phase nanomolecules with MR character, outperforming KS-DFT with the widely used XC energy functionals. Moreover, a few recent studies [64][65][66][67] on the ground-state properties of electronic systems at absolute zero have been actually performed using an approximate TAO-DFT method (i.e., TAO-DFT without the θ-dependent energy functional [37]) at some fictitious temperature θ, which should not be confused with the Mermin-Kohn-Sham method (also called finite-temperature density functional theory (FT-DFT)) [23,68] at some finite electronic temperature due to their distinctly different physical meanings (e.g., see Refs. [37,44,58] for further discussion).…”
Section: Of 18mentioning
confidence: 99%
“…On the computational side, Omist et al [ 26 ] reported the electronic properties of GNP[2, n ] (with n = 3–7) and nitrogen-doped GNP[2, n ], obtained with various electronic structure methods. Besides, Sandoval-Salinas et al [ 27 ] performed electronic structure calculations to explore the electronic properties of GNP[ m , n ] (with = 2–6). In addition, a recent computational study reported a few electronic properties of GNP[ m , n ] (with = 2–4) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%